Health education via “empowerment” digital marketing of consumer products and services: Promoting therapeutic benefits of self-care for depression and chronic pain - Huntsman, Jade L.; Bulaj, Grzegorz (Frontiers in Public Health, 2023)
Increasing health care costs and high economic burden exemplify the impact of chronic diseases on public health. Multifaceted approaches to treating chronic diseases include pharmaceutical drugs, digital therapeutics, and lifestyle medicine. Chronic diseases are largely preventable, and health promotion yields positive outcomes. However, despite positive return on investment (ROI) and cost-to-benefit ratio (CBR) for health promotion (median ROI 2.2, median CBR 14.4), commercial marketing of healthy lifestyles and self-care is limited. The objective of this perspective article is to discuss how digital marketing of consumer goods and services that support therapeutic self-care can also bridge public health and for-profit interests. We describe how “empowerment” marketing campaigns can provide evidence-based associations between products/services and self-care benefits for people living with chronic pain and depression. Such a “health education as marketing” strategy is illustrated by educational ads describing how contact with nature, music, and yoga can improve chronic pain and reduce depressive symptoms. Creating associations between health-related benefits of these activities with products (outdoor and yoga apparel, audio equipment) and services (music streaming services, music mobile apps, eco-tourism, yoga studios) that support them expand their value proposition, thus incentivizing profit-driven companies to engage in public health campaigns. Long-term success of companies that incorporate evidence-based health education as marketing and branding strategies will depend on following ethical considerations and advertising guidelines defined by consumer protection regulatory agencies, such as the Federal Trade Commission (FTC). In conclusion, integration of health education about self-care and commercial marketing can support health care outcomes and disease prevention.